Morphogenetic characteristics and management of Tanzania grass - Santos, Patricia Menezes; Balsalobre, Marcos Antônio Alvares; Corsi, Moacyr (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the effect of grazing interval and period of evaluation over tissue turnover in Tanzania grass pastures (Panicum maximum cv. Tanzania) and to ascertain if herbage accumulation rate can be used as a criterion to establish a defoliation schedule for this grass in Southeast of Brazil. A randomized block design with a split-plot arrangement was used. The effect of three grazing intervals was evaluated within seven periods between October 1995 and September 1996. Responses monitored were leaf and stem elongation rates, leaf senescence rate, stem length, and tiller density. Net herbage accumulation rate was calculated using tissue turnover data. The grazing intervals for Tanzania grass should be around 38 days between October and April (spring and early autumn) and 28 days during the reproductive phase of the grass (April/May). Between May and September (late autumn and winter), grazing interval should be around 48 days. Herbage accumulation rate is not a good criterion to establish defoliation time for Tanzania grass. Studies on the effects of stem production in grazing efficiency, animal intake and forage quality are needed to improve Tanzania grass management.